Chinese state and society in epidemic governance: A historical perspective. (27th July 2020) - Leung, Angela Ki Che
Abstract: This paper looks at the role of state and society in the history of epidemic governance in China for an appreciation of the way China manages the current COVID‐19 epidemic.